Studies on inactivated influenza vaccines - Forsyth, Jocelyn Robert Lane (Department of Medicine, 2020)
It is, perhaps, ironical. that while influenza was probably the first animal virus to be studied in detail there is still little known concerning its behaviour. In many ways it represents a model of difficult immunization problems. Now that so many of the most lethal and dramatic of the infectious diseases are susceptible to control attention is being focused upon the control of the next rank of disorders. This includes those conditions which cause ill-health and discomfort only to such an extent that the cost and severity of measures of prevention must be carefully weighed against the effects of the disease process itself. The solution of the technical, administrative and ethical problems of influenza control will, in addition, greatly assist the struggle against numerous other ailments.